Long-term changes in vigour and distribution of Banksia and Melaleuca overstorey species on the Swan Coastal Plain - Groom, Philip; Froend, R.; Mattiske, E.; Gurner, R. (2001)
Long-term changes in vigour and distribution of the dominant Banksia (5 species) and Melaleuca (1 species) overstorey species were examined within four vegetation transects overlying the Gnangara Groundwater Mound, a superficial unconfined shallow aquifer on the northern Swan Coastal Plain, Western Australia. All transects were positioned along topographical gradients and monitored over a 20-30 year period. The two co-dominant overstorey species (Banksia attenuata and B. menziesii) inhabited a range of topographical positions within the landscape, from dune crest to low lying areas, with only B. attenuata increasing its distribution (moving further downslope) within the transects over time. Both species displayed a reduction in vigour, as indicated by foliage condition, during the monitored period. Species commonly inhabiting low-lying winter-wet areas (e.g. Banksia littoralis, Melaleuca preissiana) showed the greatest loss of tree vigour in response to declining groundwater levels, with B. littoralis replaced by the more drought tolerant B. prionotes. M. preissiana populations were overall more resilient to altered groundwater regimes, responding over a much greater time period (many decades) than B. littoralis (<10 years). Overall, changes in species distribution and vigour were primarily caused by long-term declines in groundwater levels resulting from the cumulative effects of abstraction and below average annual rainfall (low groundwater recharge). Long-term distribution trends and overall observed reductions in population vigour within the transects may be a function of the species’ dependency on groundwater to fulfil its water requirements. This may explain declining vigour and tree numbers of B. ilicifolia on the Gnangara Groundwater Mound, as this species is considered an important indicator of significant long- and short-term reductions in groundwater levels.